Experiment and Prediction of Ablation Depth in Excimer Laser Micromachining of Optical Polymer Waveguides - K. F. Tamrin; S. S. Zakariyah; K. M. A. Hossain; N. A. Sheikh (Advances in Materials Science and Engineering)
Extending the data transfer rates through dense interconnections at inter- and intraboard levels is a well-established technique especially in consumer electronics at the expense of more cross talk, electromagnetic interference (EMI), and power dissipation. Optical transmission using optical fibre is practically immune to the aforementioned factors. Among the manufacturing methods, UV laser ablation using an excimer laser has been repeatedly demonstrated as a suitable technique to fabricate multimode polymer waveguides. However, the main challenge is to precisely control and predict the topology of the waveguides without the need for extensive characterisation which is both time consuming and costly. In this paper, the authors present experimental results of investigation to relate the fluence, scanning speed, number of shots, and passes at varying pulse repetition rate with the depth of ablation of an acrylate-based photopolymer. The depth of ablation essentially affects total internal reflection and insertion loss, and these must be kept at minimum for a successful optical interconnection on printed circuit boards. The results are then used to predict depth of ablation for this material by means of adaptive neurofuzzy inference system (ANFIS) modelling. The predicted results, with a correlation of 0.9993, show good agreement with the experimental values. This finding will be useful in better predictions along with resource optimisation and ultimately helps in reducing cost of polymer waveguide fabrication.